An experimental renal acidification defect in patients with hereditary fructose intolerance: II. Its distinction from classic renal tubular acidosis; its resemblance to the renal acidification defect associated with the fanconi syndrome of children with cystinosis - Morris, R. Curtis, Jr. (The Journal of Clinical Investigation, 1968)
In adult patients with hereditary fructose intolerance (HFI) fructose induces a renal acidification defect characterized by (a) a 20-30% reduction in tubular reabsorption of bicarbonate (T HCO3-) at plasma bicarbonate concentrations ranging from 21-31 mEq/liter, (b) a maximal tubular reabsorption of bicarbonate (Tm HCO3-) of approximately 1.9 mEq/100 ml of glomerular filtrate, (c) disappearance of bicarbonaturia at plasma bicarbonate concentrations less than 15 mEq/liter, and (d) during moderately severe degrees of acidosis, a sustained capacity to maintain urinary pH at normal minima and to excrete acid at normal rates. In physiologic distinction from this defect, the renal acidification defect of patients with classic renal tubular acidosis is characterized by (a) just less than complete tubular reabsorption of bicarbonate at plasma bicarbonate concentrations of 26 mEq/liter or less, (b) a normal Tm HCO3- of approximately 2.8 mEq/100 ml of glomerular filtrate, and (c) during acidosis of an even severe degree, a quantitatively trivial bicarbonaturia, as well as (d) a urinary pH of greater than 6. That the fructose-induced renal acidification defect involves a reduced H+ secretory capacity of the proximal nephron is supported by the magnitude of the reduction in T HCO3- (20-30%) and the simultaneous occurrence and the persistence throughout administration of fructose of impaired tubular reabsorption of phosphate, alpha amino nitrogen and uric acid. A reduced H+ secretory capacity of the proximal nephron also appears operative in two unrelated children with hyperchloremic acidosis, Fanconi's syndrome, and cystinosis. In both, T HCO3- was reduced 20-30% at plasma bicarbonate concentrations ranging from 20-30 mEq/liter. The bicarbonaturia disappeared at plasma bicarbonate concentrations ranging from 15-18 mEq/liter, and during moderate degrees of acidosis, urinary pH decreased to less than 6, and the excretion rate of acid was normal.